TINJAUAN MATERIAL KAYU UNTUK DRAWER (MEJA NAKAS) - Denta Mandra Pradipta Budiastomo; Nukke Sylvia (Narada : Jurnal Desain dan Seni, 2020)
Drawer (nightstand) is one of the home properties that are very important because there are also many functions of sweetening the room or can be used to store things for necessity. There was a time when night tables were considered only as their storage space built as ordinary shelves with shelves to store objects in bedrooms, schools, hospitals, and offices. The drawer is mostly made of wood but not many people know about the material used as the base for making Drawers. Therefore what will be sought in this research is anything that is light wood for Drawers or night tables, any coloring that is suitable for Drawers or nightstand, ergonomic forms for Drawers or nightstand. The method that will be used in achieving the objectives of this research is the desk research method. analyze secondary sources from books and the internet that discuss Drawer. The research objective to be achieved in this study is to reveal a study of knowing and analyzing what is light wood suitable for Drawer (night table), knowing the color and analyzing what colors are suitable for Drawer (night table), Knowing and analyzing shapes Ergonomic for Drawers (nightstand).